My fair lady ([S.l. s.n.)
A Cockney waif is transformed by a linguistics professor into an elegant lady.
Disc 1 (59 min.) -- disc 2 (57 min.) -- disc 3 (53 min.)
Based upon the musical play as produced on the stage by Herman Levin.
From a play by Bernard Shaw.
Originally released as motion picture in 1964.
VCD.
Lyrics by Alan Jay Lerner ; music by Frederick Loewe ; screenplay by Alan Jay Lerner ; produced by Jack L. Warner ; directed by George Cukor.
Audrey Hepburn, Rex Harrison.
Keywords: Musical films; Feature films